PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBING PROMPTING DAN PROBLEM BASED LEARNING DI MTsN 2 PADANGSIDIMPUAN - Sari, Lili Nur Indah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2018)
This study aims to determine the significant differences between students' mathematical problem solving abilities after using the Probing Prompting model and the Problem Based Learning learning model. This type of research uses the quasi experimental design method. The design of this study was a pretest-posttest control group design. In this design, the grouping of research samples was done randomly, the experimental class I was taught using the Probing Prompting learning model and the experimental class II was taught using the Problem Based Learning learning model before and after the treatment was given the pretest and posttest. The results obtained from the Student Problem Solving Ability test conducted on the Probing Promting learning model were 43 students and obtained an average value of 67.09 while the Problem Based Learning learning model was 44 students and an average value of 64.43 was obtained. Students 'problem solving abilities after using the Promting Probing learning model in class VIII-1 (Experiment I) Padangsidimpuan 2 MTs obtained an average score of 67.09 Problem Solving Ability with a standard deviation or diversity from the results of students' mathematical problem solving ability test of 12.778. Students 'Problem Solving Ability after using the Problem Based Learning learning model in class VIII-3 (Exp.Padangsidimpuan MTs 2 obtained the average value of students' problem solving abilities of 64.43 with a standard deviation or diversity of a student's problem solving abilities of 13.944. Based on the t-test it is known that there is no difference in the Problem Solving Ability of Students with the Probing Promting learning model in class VIII-1 (Experiment I) and the Problem Based Learning learning model in class VIII-3 (Experiment II) or in other words concluded that there is no difference in Ability Problem Solving Students who are taught using Probing Promting learning models and Problem Based Learning learning models.